Giant bronchogenic cyst with pericardial defect: a case report & literature review in Japan - Kamata, Toshiko (J Thorac Dis, 2016)
Congenital pericardial defects are a rare anomaly, found during autopsy and cardiothoracic surgery. We describe a case of a 69-year-old female, with a right-sided congenital pericardial defect associated with a giant bronchogenic cyst (BC) found during surgery. The cyst was resected and the patient developed arrhythmia following surgery. A review of the literature in Japan was performed, focusing on congenital anomalies associated with pericardial defects and its pathogenesis. We paid particular attention to complications following thoracic surgery in patients with pericardial defects and indications of pericardial reconstruction in such patients.